Annular beam high‐intensity X‐ray diffraction based on an ellipsoidal single‐bounce monocapillary. Issue 2 (10th February 2016) - Li, Fangzuo; Liu, Zhiguo; Sun, Tianxi
Abstract : An ellipsoidal single‐bounce monocapillary is employed to produce an annular X‐ray beam, and the focal construct geometry high‐intensity angular‐dispersive X‐ray diffraction technique is presented. Abstract : This short communication presents a study of the use of an annular X‐ray beam produced by an ellipsoidal single‐bounce monocapillary (ESBC) to perform focal construct geometry (FCG) high‐intensity angular‐dispersive X‐ray diffraction (ADXRD) in transmission mode. The ESBC optic effectively focused a large focal spot X‐ray source into a smaller focal spot and produced a narrowed X‐ray ring in the far‐field pattern when combined with a beam stop. A CCD imaging detector was linearly translated along the principal axis of the ESBC‐FCG and obtained the corresponding sequential images of diffraction concentric circular caustics and convergence points, which were formed by the constructive interference of a continuous set of Debye cones arising from the annular interrogation volume. Pixels from the central region of an approximately 0.6 mm 2 area were interrogated on each sequential image; as a result, a one‐dimensional diffractogram of an aluminium oxide sample was revealed. The presented ESBC‐FCG ADXRD technique shows potential for increasing the diffracted intensity and streamlining the operation of crystallographic analysis.